2009
DOI: 10.1097/ta.0b013e318187eb16
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Clinical Evaluation of Posterior Malleolar Fractures. A Systematic Review of the Literature

Abstract: No consensus in the literature was found as to which fragment size of the posterior malleolus (=posterior tibial margin) should be internally fixed. This is partially because of the lack of standardization in examining functional outcomes, making it difficult to compare results. It is not the peak pressure or changes in tibiotalar contact area, but rather the changes in peak pressure distribution that play a large role in posttraumatic arthritis development. It seems important to restore the medial and lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 40 publications
4
108
0
4
Order By: Relevance
“…Furthermore, in none of these configurations was a tendency for subluxation noted. Fitzpatrick's experimental data are supported and have been confirmed by van Bekerom's systematic review of the literature, including clinical and biomechanical publications [23]. No differences in outcome were found whether Volkmann fragments that were bigger than one-third of the joint surface were reduced and fixed or just left alone.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, in none of these configurations was a tendency for subluxation noted. Fitzpatrick's experimental data are supported and have been confirmed by van Bekerom's systematic review of the literature, including clinical and biomechanical publications [23]. No differences in outcome were found whether Volkmann fragments that were bigger than one-third of the joint surface were reduced and fixed or just left alone.…”
Section: Discussionmentioning
confidence: 67%
“…Among the fractures followed, 9 were bi-and 34 were trimalleolar fractures. There were 23 Weber type B fractures and 20 type C fractures. Four fractures were open fractures, 3 were grade 1 and 1 was grade 2 according to the Gustilo-Anderson classification [12].…”
Section: Resultsmentioning
confidence: 99%
“…However, fractures of the posterior malleolus, which usually occur in combination with lateral malleolus fractures [20,21], may alter treatment decisions even when there is minimal displacement of the fragments. Although there is still debate whether the primary role of the posterior malleolus is related to peak stress distribution or to tibiotalar stability [7,19], indications for operative intervention in cases of posterior malleolus fractures are frequently based on fragment size [7,8,10]. Accordingly, 97 % of surgeons preferred operative management for posterior malleolus fractures in one study when >50 % of the articular surface was involved [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, common combinations of minimally displaced lateral malleolus fractures with minimally displaced posterior malleolus fractures that involve <50 % of the articular surface increase the uncertainty regarding preferred treatment. Accordingly, in a recent review, no consensus was found as to which posterior malleolus fragment size should be internally fixed [19].…”
Section: Introductionmentioning
confidence: 99%
“…But studying their paper, we will discover that their arguments are based on just a limited number of personal observations and that the Volkmann dogma is grounded on very weak and thin ice-a good reason to review critically the role of the Volkmann triangle and formulate some serious doubts and provocative ideas about how to deal with these fractures today. If the recent literature [8] (and our small, personal series) is right, the Volkmann dogma might fall.…”
mentioning
confidence: 85%